KARAKTERISTIK MUTU PATI SAGU DARI PROVINSI RIAU DENGAN PERLAKUAN HEAT MOISTURE TREATMENT (HMT) - Shanti Fitriani; Evi Sribudiani; Rahmayuni ' (Jurnal Sagu, 2010)
Sago plant (Hfetroxylon sp), is one of potential |riant producing of carbohydrate in Indonesia includingthe province of Riau. Sago starch (sago) is pith extract of sago stem. To obtain a high qualit}' of sago starchneed to do modified starches. Modified starches can be done with physical treatment, such as by heating at acertain water (Heat Moisture Tk^eatment/HMT). This study aims to determine the quality and the pastingprofile of sago with and without HMT from Inderagiri Hilir district and Bengkalis, Riau province. Thisresearch was used Completely Randomized Design (RAL), which consisting 4 treatments, each treatmentperformed three repetitions and obuined 12 units experiment. The treatments were: Bengkalis Non HMTtreatment (BN), non-treatment of HMT Inderi^iri HiHr (IN), Bengkalis with HMT treatment (BP), IndragiriHilir with HMT treatment (IF). Chemical analysis carried out on the moisture content, ash content, pHmeasurements, and starch pasting profile. The results showed that HMT affect the moisture content, ashcontent and crude fiber content of sago, and do not affect the pH as well as pasting profiles of sago.